ANALISIS PRAKTIK GREENWASHING SHEIN DALAM INDUSTRI FAST FASHION BERDASARKAN PERSPEKTIF HUKUM LINGKUNGAN INDONESIA - Agnes Angelika; Naira Puspita; Keyza Naila Humaira Hermana; Rizky Akbar Maulidina (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
The fast fashion industry contributes significantly to environmental damage through the exploitation of natural resources, textile waste, and carbon emissions. Amidst increasing public awareness of environmental issues, many companies are exploiting sustainability claims as a marketing strategy, leading to greenwashing practices. This study analyzes greenwashing practices in the SHEIN case from the perspective of Indonesian environmental law and its relationship to the Sustainable Development Goals (SDGs). The method used is normative juridical with a legislative approach and case studies. The results show that although Indonesia does not yet have specific regulations regarding greenwashing, existing legal instruments in environmental protection and consumer protection can be used as a basis for action. This practice contradicts the principles of transparency, prudence, and responsibility in environmental law. In addition, greenwashing also has the potential to hinder the achievement of the SDGs, especially goals 12 and 13 related to sustainable consumption and production, as well as climate action. Therefore, strengthening regulations, increasing supervision, and more effective law enforcement are needed to prevent similar practices in the future, in line with sustainable development goals, especially in the context of the global fashion industry in Indonesia.